(untitled) (World Bulletin of Social Sciences, 2026)
The article provides a detailed study of the historical factors of the story plot. In this work, the genre characteristics of the story, the specific aspects of the plot are studied in comparison with such genres as myth, folk oral literature as fairy tales, short stories, epics, and scientific and theoretical conclusions are drawn. It is also based on the fact that the story is as ancient as the genres of the novel, short story, and novella.